LEGAL PROTECTION FOR CONSUMERS AGAINST ILLEGAL PHARMACEUTICAL DRUG SALES - Mohamad, Fiqih Ashar; Wantu, Fence; Rahim, Erman (LPPM STIH Putri Maharaja, 2024)
The purpose of this study is to provide a clear picture of the mode of selling illegalpharmaceutical drugs online, as well as to examine the form of legal protection for consumers in thesale of illegal pharmaceutical drugs online. This research was conducted at the office of the Foodand Drug Supervisory Center of Gorontalo Province. This research uses normative researchmethods but is supported by empirical data and uses a qualitative approach through descriptiveanalysis methods of secondary data. Through a legal approach, this research examines existingregulations and sanctions for lawbreakers related to illegal drugs and a conceptual approach tobuild an ideal model of legal protection. The results show that the mechanism for selling illegalpharmaceutical drugs online is carried out through various modes, including falsification ofdistribution permits, use of unregistered digital platforms, and misuse of information technology.The form of legal protection for consumers on the sale of illegal pharmaceutical drugs online mustbe strengthened through clear regulations and strict law enforcement. Although consumerprotection laws and health laws have provided a legal basis for consumers to protect themselvesfrom unfair trade practices, there are still many challenges in implementing and enforcing laws thatare less effective and have been unable to keep up with the times.